Carbon dioxide chemical absorption by solvents based on diamine and amines blend. Issue 7 (1st March 2018) - Cachaza, Alberto; Gómez‐Díaz, Diego; Montáns, Adrián; Navaza, José M.; Rumbo, Antonio
Abstract : Present work includes research about the influence of the type of amino group using one or two amine molecules on carbon dioxide chemical absorption using aqueous solutions of alkanolamines and diamines. A comparison of chemical absorption processes using aqueous solutions of two individual diamines (3‐(dimethylamino)propan‐1‐amine and 1, 3‐diaminopropane) and a mixture of amines (3‐amino‐1‐propanol and 3‐(dimethylamino)propan‐1‐ol) is reported including absorption rate curves, carbon dioxide loading, reaction mechanism or solvent regeneration to obtain useful information about the quality of each solvent for carbon dioxide separation. In general, amines blend of 3‐amino‐1‐propanol and 3‐dimethylamino‐1‐propanol, have shown a better behavior than their individual amines. Diamines and mainly 3‐dimethylamino propylamine that presents primary and tertiary amine groups in its structure, have led similar results. After these studies, 3‐dimethylamino propylamine, can be considered an appropriated amine to industrial carbon dioxide absorption process. © 2018 American Institute of Chemical Engineers AIChE J, 64: 2702–2710, 2018